2015
DOI: 10.1002/ijc.29820
|View full text |Cite
|
Sign up to set email alerts
|

Myoferlin plays a key role in VEGFA secretion and impacts tumor‐associated angiogenesis in human pancreas cancer

Abstract: Pancreatic ductal adenocarcinoma is one of the most deadly forms of cancers with no satisfactory treatment to date. Recent studies have identified myoferlin, a ferlin family member, in human pancreas adenocarcinoma where its expression was associated to a bad prognosis. However, the function of myoferlin in pancreas adenocarcinoma has not been reported. In other cell types, myoferlin is involved in several key plasma membrane processes such as fusion, repair, endocytosis and tyrosine kinase receptor activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 49 publications
1
71
0
Order By: Relevance
“…A paucity of studies demonstrates that exosomes are mediators that facilitate intercellular exchange of biomolecules, assuming an important role in cell-to-cell communication [29]. In the current study we focused on myoferlin, a membrane associated protein, which has recently been demonstrated to be pro-oncogenic in several types of cancer [21, 22, 2628, 30]. In breast cancer, in vivo tumor xenografts lacking myoferlin have been described as smaller, less invasive and less vascularized than their control counterparts [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A paucity of studies demonstrates that exosomes are mediators that facilitate intercellular exchange of biomolecules, assuming an important role in cell-to-cell communication [29]. In the current study we focused on myoferlin, a membrane associated protein, which has recently been demonstrated to be pro-oncogenic in several types of cancer [21, 22, 2628, 30]. In breast cancer, in vivo tumor xenografts lacking myoferlin have been described as smaller, less invasive and less vascularized than their control counterparts [27].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies performed in endothelial cells demonstrated that myoferlin is important for membrane repair and endocytosis [17] as well as receptor-mediated angiogenesis [1821]. In cancer, overexpression of the protein has been reported in breast, lung, and pancreatic tumors [2225], where it is associated with increased tumorigenic potential and angiogenesis [21, 2628]. Mechanistically, myoferlin has been shown to control both endocytosis (EGFR, VEGFR2, IGFR and Tie-2) and exocytosis (VEGF) of several key molecules [1821, 28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previously it has been shown that the long-term maintenance in culture of PDAC cell lines, such as BxPC-3, CFPAC-1 and PANC-1 cells 33,34 , resulted in distinct and irreversible loss of crucial genetic and biologic properties. This included the occurrence of distinct stem cell populations and complex genomic aberrations, affecting critical signaling pathways 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, C1s/C1r are reported to degrade collagen and are involved in activation of CUB domain containing proteins that regulate many aspects of cancer progression and metastasis [44]. SNAP23 is a key regulator of the membrane-membrane fusion events required for intracellular membrane traffic and has been reported to traffic matrix metalloproteases during degradation of ECM substrates, thus enabling cellular invasion [45], whilst myoferlin is involved in increased tumor associated angiogenesis [46, 47]. The differential expression of exosomal proteins both between HR and LR UM, and also between all UM and NCM may suggest basic differences in exosome biogenesis and trafficking.…”
Section: Discussionmentioning
confidence: 99%